Part XIII Of The Insurance Act 1996: Payment Of Policy Money Under A Life Insurance Policy Or Personal Accident Insurance Policy - Salim, Rafiah (Journal of Malaysian and Comparative Law, 2019)
Who benefits from policy moneys payable under a life insurance policy or a personal accident insurance policy upon the death of the policy owner? This is a question which every policy owner would want a clear answer in order to plan his estate effectively in his lifetime.